2020
DOI: 10.4111/icu.2020.61.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pathologic upgrading in Gleason score 3+4 prostate cancer: Who is a candidate for active surveillance?

Abstract: Purpose Whether active surveillance (AS) can be safely extended to patients with Gleason score (GS) 3+4 prostate cancer is highly debated. We examined the incidence and predictors of upgrading among patients with GS 3+4 disease. Materials and Methods The study involved 377 patients with biopsy GS 3+4 who underwent robot-assisted laparoscopic radical prostatectomy (RP) from 2014 to 2018 at a single institution. We analyzed the rate of GS upgrading and used logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Although we describe similar predictors, some findings should be further discussed. PI-RADS was identified as a predictor for upgrading to ISUP ≥ 3 and AP as previously reported in a single-institution study by Pham et al [25]. Moreover, ECE on mpMRI predicted AP in the subgroup with low-risk PCa and lesion volume predicted upgrading to ISUP ≥ 3 in the subgroup with favorable intermediate-risk PCa.…”
Section: Discussionsupporting
confidence: 82%
“…Although we describe similar predictors, some findings should be further discussed. PI-RADS was identified as a predictor for upgrading to ISUP ≥ 3 and AP as previously reported in a single-institution study by Pham et al [25]. Moreover, ECE on mpMRI predicted AP in the subgroup with low-risk PCa and lesion volume predicted upgrading to ISUP ≥ 3 in the subgroup with favorable intermediate-risk PCa.…”
Section: Discussionsupporting
confidence: 82%
“…Pham et al . 5 reported that tPSA, age, PI-RADS score, and PSAD were the independent predictors of GG upgrading. Yang et al .…”
Section: Discussionmentioning
confidence: 97%
“…For biopsy GG 2, our data revealed that 46.9% of patients experienced upgrading at RP among clinical T1–3 PCa. This result was consistent with the findings by Pham et al ., 5 which demonstrated an upgrading rate of 44.6% for patients with biopsy GG 2 and clinical T1–3 PCa.…”
Section: Discussionmentioning
confidence: 98%
“…This concern results in many men electing to undergo additional therapy, despite their low-grade cancer diagnosis. Their anxiety is clearly warranted as numerous studies find evidence of more aggressive disease in a subset of their patients (62)(63)(64)(65)(66). The prostate cancer can be either upgraded (i.e., the Gleason score is higher in the prostatectomy than in the biopsy) or upstaged (i.e., the tumor-node-metastasis stage is higher at time of surgery than was originally recorded).…”
Section: Targeted Verification/validation Approachesmentioning
confidence: 99%